Identifying and recording three of the important heritage sites pertaining to the history of the black people in the Free State - Twala, Chitja M. (University of the Free State, 1997)
This project is aimed at identifying historical places of interest concerning black history. A similar project has been done before by Tshidiso Ratithlare. This shows that black history has been ignored for a very long time. This has brought about a lack of self-identification and confidence in black people and also implanted an inferiority complex towards their own history. The identification and preservation of the heritage sites is an emotional issue which can either rally or divide people. The story of site tells, can be one person's dre.am and another's nightmare. South Africa is a particularly fragmented society, and many people clutch onto the safety and familiarity of the exclusive and divisive symbols at hand. Sites themselves seek to include group members in a shared understanding of culture and heritage. Becoming a more democratic society means, inter alia, finding new heritage sites that reflect and reinforce this new identity. However, heritage sites should not be allowed to become a political football and arouse conflict, and great circumspection should be exercised with the choice of heritage sites. The sites discussed in this dissertation are not only of interest or importance to blacks, but also to the entire population of South Africa, particularly of the Free State province. In the Free State province there is a wealth of historical resources still to be tapped. History as a discipline must proceed alongside adjacent disciplines such as archaeology, ethnology, geography, anthropology and the Expertise of the National Monuments Council and National Museums must be utilized.
Dissertation (B.A.Honns. (History))--University of the Free State, 1997
Keywords: Black people -- South Africa -- Free State -- History; Historic sites -- South Africa -- Free State -- History; Cultural property -- South Africa -- Free State